USŁUGI W OGÓLNYM INTERESIE GOSPODARCZYM A REGUŁY OCHRONY KONKURENCJI W UNII EUROPEJSKIEJ - Kosiński, Eryk (Wydział Prawa i Administracji UAM, 2005)
The general EC competition provisions, or the anti-competitive agreements are contained in the new 81-86 (former art. 85-90) of the Treaty on the EU of 25 March 1957 (The Treaty of Rome). The EU competition regulations apply solely to the anti-competitive agreements which may infringe free trade between member states, and, as such, they concern undertakings. The EU competition rules are binding in all spheres of economic activity, except for the exceptional cases where the Treaty excludes their application. Those exclusions, however, are few. One of the general exclusions is provided in the new art. 86 clause. 2 (former art. 90 clause 2) of the Treaty. It applies to those undertakings which have been given by the state the status of undertakings rendering services of general economic interest, or undertakings that constitute an element of a state monopoly, bringing a certain revenue. The notion of a state monopoly bringing revenues, or a fiscal monopoly, does not pose any major interpretation problems. However, the notion of services of general economic interest is already a specific concept that has been introduced to the community law. Moreover, it should be stressed that services of general economic interest constitute one of the prinicipal rules of the Community. Similar, or derivative, notions to those above are public utility, public services and universal services. Services of general interest is a broader concept, to be found in large network-type sectors such as transport, postal services, communication or energy. Recognition of a certain type of services as services of general economic interset entails certain public service obligations imposed on the providers of those services.
SERVICES OF GENERAL ECONOMIC INTEREST VS THE COMPETITION LAW PROVISIONS IN THE EUROPEAN UNION